Re: A Randomized Prospective Double-Blind Comparison Trial of Clomiphene Citrate and Anastrozole in Raising Testosterone in Hypogonadal Infertile Men - Emre Bakırcıoğlu (Journal of Urological Surgery, 2016)
It has been reported that the prevalence of low testosterone (<300 ng/ml) in infertile men was as high as 41% and low testosterone did not always correlate with impaired seminal parameters (1). Although previous studies have shown that clomiphene citrate (CC) and anastrozole (AZ) were effective in increasing testosterone levels, randomized double blind comparisons are lacking. In this study, the authors aimed to investigate the equivalence of CC versus AZ with respect to improvement in testosterone levels in hypogonadal infertile men. It was shown that there was a significantly larger increase in T level in CC group vs AZ group at 6 and 12 weeks whereas estradiol levels increased in CC group compared to AZ group. Both groups did not demonstrate significant changes in seminal parameters or patient-reported outcomes, This study shows that CC would be a better choice to increase testosterone levels for hypogonadal men with low estradiol levels.